2016
DOI: 10.1126/scitranslmed.aaf1061
|View full text |Cite
|
Sign up to set email alerts
|

Human polyclonal immunoglobulin G from transchromosomic bovines inhibits MERS-CoV in vivo

Abstract: As of 13 November 2015, 1618 laboratory-confirmed human cases of Middle East respiratory syndrome coronavirus (MERS-CoV) infection, including 579 deaths, had been reported to the World Health Organization. No specific preventive or therapeutic agent of proven value against MERS-CoV is currently available. Public Health England and the International Severe Acute Respiratory and Emerging Infection Consortium identified passive immunotherapy with neutralizing antibodies as a treatment approach that warrants prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 50 publications
0
116
0
1
Order By: Relevance
“…However, the single clone antibody raises the concern of viral escape mutant when applied to human. Administration of transchromosomic bovine human immunoglobulins (Luke et al, 2016) or dromedary immune serum resulted in rapidly viral clearance in infected mouse lungs. The disadvantage of these antibodies is that these animals are not readily available.…”
Section: Passive Transfer Of Equine Antibodies Protected Mers-cov Infmentioning
confidence: 99%
“…However, the single clone antibody raises the concern of viral escape mutant when applied to human. Administration of transchromosomic bovine human immunoglobulins (Luke et al, 2016) or dromedary immune serum resulted in rapidly viral clearance in infected mouse lungs. The disadvantage of these antibodies is that these animals are not readily available.…”
Section: Passive Transfer Of Equine Antibodies Protected Mers-cov Infmentioning
confidence: 99%
“…Active immunizations with adjuvanted, multi-eptitope bacterial vaccines are in development, as are monoclonal and polyclonal antibodies, as passive therapies against bacterial pathogens [911]. Transchromosomic cattle have been developed that can deliver high volumes of high quality, human polyclonal antibodies against bacterial and viral antigens [11].…”
Section: Advanced Immunotherapiesmentioning
confidence: 99%
“…Active immunizations with adjuvanted, multi-eptitope bacterial vaccines are in development, as are monoclonal and polyclonal antibodies, as passive therapies against bacterial pathogens [911]. Transchromosomic cattle have been developed that can deliver high volumes of high quality, human polyclonal antibodies against bacterial and viral antigens [11]. Monoclonal antibodies can be designed with advantageous features and half-lives that can opsonize bacteria or inhibit virulence factors without the need for antibiotics [9, 10].…”
Section: Advanced Immunotherapiesmentioning
confidence: 99%
“…Platforms are being developed to rapidly discover monoclonal antibodies, either from fully human convalescent blood or from transgenic animals, which can be manufactured on a large scale and are likely to have a good safety profile. The most advanced immunotherapeutic for MERS-CoV uses a transchromosomal bovine production system to produce fully human polyclonal MERS-CoV antibodies; a phase I study of this produce was recently implemented ( 57 ; https://clinicaltrials.gov/ct2/show/NCT02788188). Preliminary results from immunoprophylaxis or treatment studies have shown efficacy of fully human monoclonal or polyclonal antibodies in MERS-CoV-infected mice and NHPs (Table 4).…”
Section: Therapeutic Drugsmentioning
confidence: 99%